Estimation and Analysis of Development and Manufacturing Cost of ITB Mushika Race Car with Parametric Method - Ferdinand, Yonas
Estimation of development and manufacture cost is an approximation to estimate total cost needed to produce some product from the start of the product designing to the end of the production of that product. Traditionally, estimation done by analytical method. In analytical method, a list about anything that estimated to be needed to make the product is made. Although this method is relatively simple, it consume relatively much time and money because it require data from field about things that needed and relatively much amount of data needed. To solve that problem, parametric method is developed. In this method, cost estimation done with mathematic equation based on certain parameters. As the result, it need relatively few data to make estimation compared to analytical method thus save more time and money. By using this method, estimation process is expected to be more effective. In this research, a cost estimation by parametric method done to ITB Mushika Team’s Formula SAE Race Car. The cost estimation result will be compared to cost accounting result of the actual ITB Mushika Team’s Formula SAE Race Car to analize the validity of that cost accounting result. The analisys result could determine whether that cost accounting result already valid or not and the correction that could be done to make better cost accounting result. The conclusion is the cost accounting result of ITB Mushika Team’s Formula SAE Race Car has a lot of mistakes and does not include all the cost spend.